2019
DOI: 10.3746/pnf.2019.24.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ginsenosides and Antioxidant Activities in the Roots, Leaves, and Stems of Hydroponic-Cultured Ginseng (Panax ginseng Meyer)

Abstract: There has been very little reported on ginsenoside composition and antioxidant activity of hydroponic-cultured ginseng roots (HCR), leaves (HCL), and stems (HCS). We profiled 6 ginsenoside compounds in HCR, HCL, and HCS using high-performance liquid chromatography. Antioxidative activity of HCR, HCL, and HCS were evaluated using total phenolic content (TPC) and total flavonoid content (TFC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical-scavenging activity assays, and ferric reducing antioxidant power (FRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…In addition, there was a large amount contained in soil-cultured PGSs [ 29 ] and mountain-cultivated ginseng sprouts [ 24 ]. Our results are similar to those of prior studies, which showed that Rg1 and Re were the major ginsenoside compounds in hydroponic-cultured ginseng and soil-cultured ginseng, respectively [ 5 , 6 , 30 ]. We expected identified Rg1 and Re to be the critical compounds between the DWC and the SSC systems in a plant factory.…”
Section: Resultssupporting
confidence: 92%
“…In addition, there was a large amount contained in soil-cultured PGSs [ 29 ] and mountain-cultivated ginseng sprouts [ 24 ]. Our results are similar to those of prior studies, which showed that Rg1 and Re were the major ginsenoside compounds in hydroponic-cultured ginseng and soil-cultured ginseng, respectively [ 5 , 6 , 30 ]. We expected identified Rg1 and Re to be the critical compounds between the DWC and the SSC systems in a plant factory.…”
Section: Resultssupporting
confidence: 92%
“…The changes in bioactive phytochemicals depend on biological (e.g., organ, growth and development stages, and age) 2 , 9 , 47 , 55 , 56 and environmental factors (e.g., stress, light quality, and cultural practices) 4 , 14 , 19 , 49 , 57 , 58 . In our study, NO 3 ‒ in the PTW, together with K + , was involved in the enhanced free amino acid and ginsenoside contents in the P. ginseng sprout.…”
Section: Resultsmentioning
confidence: 99%
“…Ginsenosides are widely distributed in roots, leaves, flowers, fruits and seeds of P. ginseng , and more than 100 ginsenosides have been isolated and identified. In recent years, increasing studies on chemical, pharmacological and clinical aspects have proved that the pharmacological action of ginsenoside isolated from the stems and leaves of P. ginseng (GSLS) is similar to that from the roots (Lee et al, 2017; Song et al, 2019). Importantly, not only the ginsenoside content of the stems and leaves of P. ginseng is significantly higher than that in ginseng roots, but also the commercial price is also significantly higher than that.…”
Section: Introductionmentioning
confidence: 99%